The Abra State Institute of science and technology main campus library - Villalon, Eva Flor B. (City of San Fernando, La Union : [s.n.], 2015)
The main thrust of the study was to assess the extent of provision of the Abra State Institute of Science and Technology (ASIST) Main Campus Library along the AACCUP Standards and the level of satisfaction of users on the delivery of library services and facilities as bases for a three-year library development plan (2015-2018). This study utilized the descriptive method of research with the use of questionnaires as tools. Frequency counts, weighted mean and ranking were used to treat the data. The respondents were the external evaluator, faculty and students of ASIST Main Campus Library in Lagangilang, Abra during the School Year 2014-2015, a total of 225. the data gathered revealed that the extent of provision of ASIST Main Campus Library on the AACCUP Library Standards along personnel, collection, services and utilization, physical set-up and facilities, financial support and linkages was moderate and the area of administration had a descriptive rating of much provided. The level of satisfaction on the library services and facilities both for faculty and students was moderate. The extent of provision along AACCUP Standards and on the extent of satisfaction on the library services and facilities were considered to be weaknesses. Based on the findings, the ASIST Library Main Campus has inadequate number of collections and minimal facilities. There is a need to improve especially on the collection, organization and preservation, services and utilization, physical set-up and facilities, financial support and linkages. In view of the findings and conclusions, it was recommended that ASIST Main Campus Library should adopt the validated three-year development plan to improve the identified weaknesses of the library. The chief librarian of ASIST Main Campus Library should prepare an action plan for the implementation of the three-year development plan.
Bibliography: pages 108-110.
CHED-La Union
Keywords: Academic libraries